1985
DOI: 10.1093/jac/16.1.87
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of ciprofloxacin in patients with impaired renal function

Abstract: Pharmacokinetics of ciprofloxacin after single oral administration of 250 mg were studied in patients with and without renal failure. Ciprofloxacin concentrations were measured by HPLC. The elimination half-life was 8.7 +/- 0.9 h (mean +/- S.E.M.) in six renal failure patients not on haemodialysis, as compared to 4.4 +/- 0.2 h in six patients with normal renal function. The urinary recovery of unchanged ciprofloxacin was 5.3 +/- 1.7% of dose over 24 h in the renal failure patients, as compared to 37.0 +/- 3.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
18
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 0 publications
4
18
1
Order By: Relevance
“…The estimated mean fluoroquinolone clearances (55.0 mL/min for ciprofloxacin and 48.3 mL/min for levofloxacin with an effluent rate of 83 mL/min) by PIRRT in the present study Reference flow rate used in this study were higher than those reported (13.3-41.7 mL/min for ciprofloxacin and 11.0-27.6 mL/min for levofloxacin) in CRRT that used lower effluent flows of 17-30 mL/min (Table 5) [30-34, 36, 37]. In contrast, our calculated PIRRT clearances were also lower than those published in IHD with effluent flow rates of 500-600 mL/min [51,52]. The levofloxacin clearance by PIRRT in this present study was similar to the clearance reported in five patients with extended daily dialysis (48.…”
Section: Discussioncontrasting
confidence: 80%
“…The estimated mean fluoroquinolone clearances (55.0 mL/min for ciprofloxacin and 48.3 mL/min for levofloxacin with an effluent rate of 83 mL/min) by PIRRT in the present study Reference flow rate used in this study were higher than those reported (13.3-41.7 mL/min for ciprofloxacin and 11.0-27.6 mL/min for levofloxacin) in CRRT that used lower effluent flows of 17-30 mL/min (Table 5) [30-34, 36, 37]. In contrast, our calculated PIRRT clearances were also lower than those published in IHD with effluent flow rates of 500-600 mL/min [51,52]. The levofloxacin clearance by PIRRT in this present study was similar to the clearance reported in five patients with extended daily dialysis (48.…”
Section: Discussioncontrasting
confidence: 80%
“…Normally, 30 to 50% of ciprofloxacin is eliminated through hepatic metabolism and biliary excretion. It has been demonstrated that ciprofloxacin CL S does not always correlate well with creatinine clearance (1,6,11,23,26), and it has been suggested that increases in biliary clearance may effectively compensate for a reduction in renal clearance in patients with renal impairment (12,13,14). In the present study, 5 of the 10 patients receiving ciprofloxacin also had severe hepatic impairment.…”
mentioning
confidence: 44%
“…Total systemic clearance of ciprofloxacin in this patient population was noted to be highly variable, ranging from 0.34 to 1.70 ml/min/kg (compared to 7 to 8 ml/min/kg in patients with normal renal function) (1,6,11,23,26). This could possibly be attributed to variability in nonrenal mechanisms of drug clearance, as well as variations in the efficiency of clearance via CRRT.…”
mentioning
confidence: 83%
“…In patients with renal dysfunction there was slower elimi nation leading to longer half-life values and an increase in the area under the curve (AUC; 0-24 h) values [Boelaert et al, 1985].…”
Section: Introductionmentioning
confidence: 99%